Covalent organic framework material containing multiple redox active groups and preparation method and application thereof
By introducing thiazole groups into the polycarbonyl nitrogen-rich material, a multioxidation-reducing active group nitrogen-rich COF material is constructed, and the cycling stability and capacity of existing air self-charged water-based zinc ion batteries are solved, thereby achieving efficient air self-charge and excellent electrochemical performance.
Patent Information
- Application Number
- CN202311738324.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-12-18
AI Technical Summary
The existing air-charged water-based zinc ion batteries have low cycling stability and capacity, and the synthesis method is complex.
Developed a multioxidation-reducing active group nitrogen-rich COF material, and constructed a covalent organic framework material by introducing thiazole groups into a polycarbonyl nitrogen-rich material, and synthesized by solvothermal method.
It has achieved high discharge specific capacity, excellent cycle stability and excellent air self-charging performance, and the synthesis method is simple, low cost and good reproducibility.
Smart Images

Figure BDA0004612236700000031 
Figure BDA0004612236700000032 
Figure BDA0004612236700000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of synthesis of electrode materials, and particularly relates to a type of nitrogen-rich COF with multiple oxidation-reduction active groups and air self-charging performance for positive electrode materials of aqueous zinc ion batteries and a preparation method thereof. Background Art
[0002] With the development of technology, people are becoming more and more dependent on electricity. Rechargeable batteries are an effective system for storing electrical energy. However, there are special situations where it is impossible to provide external power to charge the battery, such as power outages or when there is no external power supply in the wild. This limits the application of rechargeable batteries, causing many devices to fail to work properly due to lack of power. In particular, wearable electronic products are most likely to encounter this situation when used outdoors. In order to overcome this situation, many self-charging power systems have been developed, such as solar energy, mechanical energy, and thermal energy, but the use of these external energy sources will always be limited by the natural environment, weather and other factors. But air is everywhere and always exists, and self-charging through spontaneous redox reactions with oxygen in the air will effectively solve this problem.
[0003] Aqueous zinc-ion batteries (AZIBs) have the advantages of low cost, safety and environmental protection that lithium-ion batteries do not have. At the same time, the zinc anode has a low redox potential (-0.76 V (relative to standard hydrogen electrode) and a high theoretical specific capacity (820 mAh g -1 ). These make it have good development prospects in wearable electronics and large-scale energy storage. Therefore, combining air with AZIB is an effective way to obtain self-rechargeable batteries. At present, some air self-charging AZIBs have been developed, but related research is still in its infancy, usually with problems such as insufficient capacity and low cycle number. For example, in 2020, Niu et al. reported an air-rechargeable AZIB based on CaVO positive electrode, in which the discharged positive electrode (CaZn 3.6VO) can undergo redox reaction with O2 in the air to achieve air self-charging (Nat. Commun. 2020, 11, 2199). Recently, they also constructed an air self-charging AZIB based on BQPH organic positive electrode (J.Am.Chem.Soc.2022, 23, 144). However, the cyclic stability of the above two air self-charging AZIBs is poor (can only maintain four to five cycles). Therefore, it is a very important task to construct an air self-charging AZIB with higher capacity and excellent cyclic stability. At present, many studies have shown that aromatic compounds containing carbonyl and imino groups (C=O / C=N) as positive electrode materials exhibit excellent electrochemical properties (Chem.Eng.J.2022, 431(3), 134253). When several COF materials studied in invention patents such as CN202210723658.X and CN202310900555.0 are used as positive electrode materials for aqueous zinc batteries, the capacity of their assembled batteries is 20Ag -1 Only 50mAh g -1 Around, the cycle stability also needs to be further improved. And no air self-charging test was performed in these invention patents. Although air self-charging detection is involved in two materials in CN202310171550.9, its capacity and cycle stability need to be further improved. And the COF materials in previous studies were synthesized by the reflux method, which is a relatively complicated synthesis method.
[0004] Compared with CN114976297A and CN116925355A, the multi-oxidation-reduction active group nitrogen-rich COF material of the present invention has a higher -1 Up to 100mAh g -1 Compared with CN116425974A, the S atoms of the two materials of the present invention exist in the form of thiazole rings, which expands the π-conjugated structure, so that the two COF materials of the present invention have better cycle stability as positive electrodes than the two materials in CN116425974A. At the same time, the air self-charging performance of the two materials of the present invention is significantly better than that of the two materials of the above-mentioned patent disclosure. In addition, the present invention uses a thick-walled reaction bottle to adopt a solvothermal method for synthesis, which is simpler and more convenient to operate than the reflux method. Summary of the invention
[0005] In order to solve the above problems, the present invention further improves the energy storage performance of the battery and continuously develops and expands applicable safe and environmentally friendly organic positive electrode materials. The present invention introduces thiazole groups into polycarbonyl nitrogen-rich materials to construct two covalent organic framework (COF) materials containing multiple redox active groups (C=O / C=N / thiazole groups). We found that the aqueous zinc battery prepared with these two COFs as positive electrode materials not only has high discharge specific capacity, high energy density and excellent cycle stability, but also has excellent performance in air self-charging, and the synthesis is simple by using a thick-walled reaction bottle and a solvothermal method.
[0006] The present invention provides a type of multi-oxidation-reduction active group nitrogen-rich COF for aqueous zinc ion battery positive electrode materials and a preparation method thereof. The structural formula of the COF material is:
[0007] HTBD-COF:
[0008]
[0009] HTDAT-COF:
[0010]
[0011] The present invention also provides a method for synthesizing the nitrogen-rich compound: the synthesis is carried out by using a thick-walled reaction bottle and a solvent thermal method.
[0012] The synthesis reaction equation involved in the present invention is as follows:
[0013]
[0014] Solvothermal synthesis method Specifically, add 2,6-diaminobenzo[1,2-d,4,5-d']dithiazole or 1,3,4-thiadiazole-2,5-diamine, hexaazatriphenylene hexacarboxylic acid trianhydride and organic solvent into a thick-walled reaction bottle, fully dissolve and disperse them evenly, and then perform dehydration condensation reaction by solvent thermal method. After the reaction is completed, cool to room temperature and filter, wash with deionized water 2-3 times, and vacuum dry to obtain the product, which is HTBD-COF / HTDAT-COF;
[0015] Among them, HTBD-COF is a COF material with multiple redox active groups and nitrogen-rich properties generated by the reaction of 2,6-diaminobenzo[1,2-d,4,5-d']dithiazole (BETD) and hexaazatriphenylene hexacarboxylic acid trianhydride (HHAT); HTDAT-COF is a COF material with multiple redox active groups and nitrogen-rich properties generated by the reaction of 1,3,4-thiadiazole-2,5-diamine (DAT) and hexaazatriphenylene hexacarboxylic acid trianhydride.
[0016] The molar ratio of 2,6-diaminobenzo[1,2-d,4,5-d']dithiazole or 1,3,4-thiadiazole-2,5-diamine to hexaazatriphenylene hexacarboxylic acid trianhydride is 1.5:1.
[0017] The reaction solvent is N,N-dimethylformamide or 1-methyl-2-pyrrolidone. The reaction temperature is 120-160°C. The reaction time is 4-7 days.
[0018] After the reaction is completed, the mixture is cooled to room temperature and filtered using a sand core funnel, washed with deionized water for 2-3 times, and vacuum dried to obtain the multi-oxidation-reduction active group nitrogen-rich COF material.
[0019] The method for synthesizing the nitrogen-rich COF material with multiple oxidation-reduction active groups is simple, has high yield, low cost and good reproducibility.
[0020] The above-mentioned nitrogen-rich COF material with multiple redox active groups is used as a positive electrode material for aqueous zinc ion batteries.
[0021] The application of the above-mentioned nitrogen-rich COF with multiple redox active groups in the preparation of aqueous zinc ion batteries with air self-charging capability.
[0022] Furthermore, the electrode sheet of the nitrogen-rich COF with multiple redox active groups is used as the positive electrode, the zinc sheet is used as the negative electrode, the glass fiber membrane is used as the separator, and the ZnSO4 aqueous solution is used as the electrolyte to be assembled into a button battery or a flexible battery.
[0023] The electrode sheet prepared by the nitrogen-rich COF with multiple redox active groups is as follows: HTBD-COF / HTDAT-COF, battery conductive agent and adhesive are mixed and ground in a mass ratio, and an appropriate amount of dispersant (such as 1-methyl-2-pyrrolidone) is added and ground again, and then evenly coated on the current collector and vacuum dried to form an electrode sheet.
[0024] Compared with the prior art, the present invention has the following characteristics:
[0025] The multi-oxidation-reduction active group nitrogen-rich COF material synthesized by the present invention has a covalent framework network structure and a π-conjugated structure, which effectively solves the problem of dissolution of organic small molecule materials in electrolytes, so that the Zn / / HTBD-COF and Zn / / HTDAT-COF batteries assembled with this type of derivative COF electrode material have good cycle stability. At the same time, the presence of multiple active groups also enables it to have a higher capacity. At 20Ag -1 The capacity can reach 100 mAh g at high current density. -1The above. The assembled flexible Zn / / HTBD-COF and flexible Zn / / HTDAT-COF batteries can maintain almost the same capacity when bent and folded, and have great potential in the application field of wearable electronic devices. More importantly, the flexible Zn / / HTBD-COF and flexible Zn / / HTDAT-COF batteries can spontaneously undergo redox reactions with oxygen in the air to achieve air self-charging, have excellent self-charging capacity, can be cycled multiple times without voltage attenuation, and can also switch back and forth between air self-charging and external power charging and operate well, which makes the batteries made of the two materials of the present invention have excellent development prospects in emergency use in the wild. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram of the components of a button battery;
[0027] Figure 2 This is a diagram of the components of a flexible battery;
[0028] Figure 3 The structural formula of the nitrogen-rich HTBD-COF with multiple redox-active groups;
[0029] Figure 4 This is the solid-state NMR carbon spectrum of the nitrogen-rich HTBD-COF with multiple redox-active groups;
[0030] Figure 5 This is the infrared spectrum of nitrogen-rich HTBD-COF with multiple redox active groups;
[0031] Figure 6 This is the Raman spectrum of the nitrogen-rich HTBD-COF with multiple redox active groups;
[0032] Figure 7 Thermogravimetric curve of nitrogen-rich HTBD-COF with multiple redox active groups;
[0033] Figure 8 The nitrogen adsorption-desorption and pore size distribution curves of nitrogen-rich HTBD-COF with multiple redox active groups;
[0034] Fig. 9 Cyclic voltammograms of nitrogen-rich HTBD-COF button cells with multiple redox active groups at different scan rates;
[0035] Fig.10 This is the rate performance diagram of the nitrogen-rich HTBD-COF button cell with multiple redox active groups;
[0036] Fig.11The charge and discharge curves of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF button battery at different current densities;
[0037] Fig.12 The multi-redox active group nitrogen-rich HTBD-COF button cell was developed at 2Ag -1 Cycling stability diagram at different current densities;
[0038] Fig.13 The energy density and power density diagram of the nitrogen-rich HTBD-COF button cell with multiple redox active groups;
[0039] Fig.14 This is the solubility diagram of nitrogen-rich HTBD-COF with multiple redox-active groups;
[0040] Fig.15 This is the AC impedance diagram of the nitrogen-rich HTBD-COF button cell with multiple redox active groups;
[0041] Fig.16 The assembly diagram of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery;
[0042] Fig.17 This is the rate performance diagram of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery;
[0043] Fig.18 The charge and discharge curves of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery at different current densities;
[0044] Fig.19 A multi-redox active group nitrogen-rich HTBD-COF flexible battery at 2Ag -1 Cycling stability diagram at different current densities;
[0045] Fig. 20 The cycling stability diagram of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery at different folding angles;
[0046] Fig.21 The charge and discharge curves of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery at different folding angles;
[0047] Fig. 22 The energy density and power density diagram of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery;
[0048] Fig.23 This is a comparison chart of the self-charging of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery in an air-exposed environment and an air-isolated environment;
[0049] Fig.24 This is a diagram of the free switching of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery under constant current charge and discharge / air self-charging mode;
[0050] Fig.25 This is the cycling stability diagram of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery under different shelf time in air environment;
[0051] Fig.26 The discharge capacity diagram of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery after air self-charging for different times;
[0052] Fig. 27 The capacity-voltage diagram of the nitrogen-rich HTBD-COF flexible battery with multiple redox active groups under different air self-charging times;
[0053] Fig.28 The discharge capacity curves of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery at different current densities after 23h of air self-charging;
[0054] Fig.29 This is a bar graph of the discharge capacity of the multi-oxidation-reduction active group nitrogen-rich HTBD-COF flexible battery at different current densities after 23 hours of air self-charging;
[0055] Fig.30 The structural formula of nitrogen-rich HTDAT-COF with multiple redox-active groups;
[0056] Fig.31 This is the solid-state NMR C spectrum of the nitrogen-rich HTDAT-COF with multiple redox-active groups;
[0057] Fig.32 This is the infrared spectrum of nitrogen-rich HTDAT-COF with multiple redox active groups;
[0058] Fig.33 This is the Raman spectrum of nitrogen-rich HTDAT-COF with multiple redox active groups;
[0059] Fig.34 Thermogravimetric curve of nitrogen-rich HTDAT-COF with multiple redox active groups;
[0060] Fig.35 The nitrogen adsorption-desorption and pore size distribution curves of nitrogen-rich HTDAT-COF with multiple redox active groups;
[0061] Fig.36Cyclic voltammograms of nitrogen-rich HTDAT-COF button cells with multiple redox active groups at different scan rates;
[0062] Fig.37 This is the rate performance diagram of the nitrogen-rich HTDAT-COF button cell with multiple redox active groups;
[0063] Fig.38 The charge and discharge curves of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF button battery at different current densities;
[0064] Fig.39 The multi-redox active group nitrogen-rich HTDAT-COF button cell was developed at 2Ag -1 Cycling stability diagram at different current densities;
[0065] Fig.40 The energy density and power density diagram of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF button cell;
[0066] Fig.41 This is the solubility diagram of nitrogen-rich HTDAT-COF with multiple redox active groups;
[0067] Fig.42 This is the AC impedance diagram of the nitrogen-rich HTDAT-COF button cell with multiple redox active groups;
[0068] Fig.43 The assembly diagram of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery;
[0069] Fig.44 This is the rate performance diagram of the nitrogen-rich HTDAT-COF flexible battery with multiple redox active groups;
[0070] Fig.45 The charge and discharge curves of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery at different current densities;
[0071] Fig.46 A multi-redox active group nitrogen-rich HTDAT-COF flexible battery at 2Ag -1 Cycling stability diagram at different current densities;
[0072] Fig.47 The cycling stability diagram of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery at different folding angles;
[0073] Fig.48 The charge and discharge curves of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery at different folding angles;
[0074] Fig.49 Energy density and power density diagram of multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery;
[0075] Fig.50 This is a comparison chart of the self-charging of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery in an air-exposed environment and an air-isolated environment;
[0076] Fig.51 This is a diagram of the free switching of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery under constant current charge and discharge / air self-charging mode;
[0077] Fig.52 This is the cycling stability diagram of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery under different shelf time in air environment;
[0078] Fig.53 The discharge capacity diagram of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery after air self-charging for different times;
[0079] Fig.54 The capacity-voltage diagram of the nitrogen-rich HTDAT-COF flexible battery with multiple redox active groups under different air self-charging times;
[0080] Fig.55 The discharge capacity curves of the multi-oxidation-reduction active group nitrogen-rich HTDAT-COF flexible battery at different current densities after 23h of air self-charging;
[0081] Fig.56 This is a bar chart of the discharge capacity of the nitrogen-rich HTDAT-COF flexible battery with multiple redox active groups at different current densities after 23 hours of air self-charging. DETAILED DESCRIPTION
[0082] The present invention will be further described below by means of specific examples.
[0083] Example 1
[0084] 30 mL of N,N-dimethylformamide (DMF) was added to a 48 mL thick-walled reaction bottle, and 2,6-diaminobenzo[1,2-d,4,5-d']dithiazole (2.25 mmol 0.4995 g) and hexaazatriphenylene hexacarboxylic acid trianhydride (purchased from McLean) (1.5 mmol 0.6663 g) were added at the same time. After sufficient dissolution and dispersion, the thick-walled reaction bottle was vacuum treated and kept at 125°C for 4 days. After the reaction was completed, it was washed with deionized water for 3 times, and the solid was collected by suction filtration and vacuum dried at 100°C for 12 hours to obtain a multi-oxidation-reduction active group nitrogen-rich COF material HTDAT-COF with a yield of 40%.
[0085] The active material of HTBD-COF as the positive electrode material is mixed with Ketjen black and binder (PVDF) in a certain proportion. Among them, HTBD-COF: Ketjen black: binder (PVDF) = 30%: 60%: 10% (mass ratio) shows the best electrochemical performance. After the three are mixed and ground for 2 hours, an appropriate amount of 1-methyl-2-pyrrolidone (NMP) is added and ground again for 0.5 hours, and then it is evenly coated on a titanium mesh and dried in a vacuum at 80°C overnight to make an electrode sheet. The electrode sheet is used as the positive electrode, the zinc sheet is used as the negative electrode, the glass fiber membrane (Shanghai Bangtian Industrial Co., Ltd., the same below) is used as the separator, and 2 mol L -1 The ZnSO4 aqueous solution is used as the electrolyte to assemble button batteries and flexible batteries (see the specific components for details). Figure 1-2 ) and investigated its electrochemical performance. Fig. 9 Cyclic voltammograms of button cells at different scan rates; Fig.10 This is the rate stability diagram of button cells; Fig.11 The charge and discharge curves of button cells at different current densities are shown in Figure 2. -1 The capacity can reach 617mAh g -1 , at 20Ag -1 The lower capacity is still 100mAh g -1 ; Fig.12 This is the cycle stability diagram of the button battery, and the capacity retention rate is 76%; Fig.13 This is the energy density and power density diagram of the button battery. When the power density is 8.9Wkg -1 The energy density can reach 110Wh kg -1 ;
[0086] Fig.18 The charge and discharge curves of flexible batteries at different current densities are shown in Figure 2. -1 The capacity can reach 445mAh g -1 , at 20Ag -1 The capacity is still 164mAh g -1 ; Fig.19 This is the cycling stability diagram of the flexible battery, with a capacity retention rate of 59%; Fig. 20 This is the cycle stability diagram of the flexible battery at different folding angles, and the capacity retention rate is 94%; Fig. 22 Energy density and power density diagram of flexible batteries, with the highest power density reaching 279mW cm -1 The maximum energy density can reach 6.3mWhcm -1 ; Fig.25 This is the cycle stability performance diagram of the flexible battery in the air self-charging-constant current discharge mode, and the voltage can be cycled for more than 8 cycles with almost no voltage decay; Fig.26 The discharge capacity of the flexible battery under different storage time in air environment is 85 mAh g after 0.5 h of storage. -1 After 23 hours of storage, the capacity can reach 389mAh g -1 (0.5Ag -1 )); Fig. 27 The capacity-voltage diagram of the flexible battery under air self-charging at different current densities. The voltage is 0.4V after 0.5h and can reach 1.15V after 23h. Fig.28 The discharge capacity of the flexible battery at different current densities after 23h of air self-charging. -1 The discharge capacity can reach 389mAh g -1 ,20Ag -1 The discharge capacity is still 105mAh g -1 .
[0087] Example 2
[0088] The experimental method was the same as that in Example 1, except that the raw material p-2,6-diaminobenzo[1,2-d,4,5-d']dithiazole was replaced with 1,3,4-thiadiazole-2,5-diamine (2.25 mmol, 0.261 g) to obtain a multi-oxidation-reduction active group nitrogen-rich COF material HTDAT-COF with a yield of 42%.
[0089] The method of assembling button cells and flexible batteries using HTDAT-COF as the active material of the positive electrode material is the same as in Example 1, that is, HTBD-COF is replaced with HTDAT-COF, and the electrode sheet preparation and battery preparation methods are exactly the same as in Example 1, and their electrochemical properties are examined.
[0090] Fig.38 The charge and discharge curves of button batteries at different current densities are shown in Figure 2. -1 The capacity can reach 603mAh g -1 , at 20Ag -1 The capacity is still 117mAh g-1 ; Fig.39 This is the cycle stability diagram of the button battery, and the capacity retention rate is 76%; Fig.40 This is the energy density and power density diagram of the button battery. When the power density is 10.3Wkg -1 The energy density can reach 124Whkg -1 ;
[0091] Fig.45 The charge and discharge curves of flexible batteries at different current densities are shown in Figure 2. -1 The capacity can reach 320mAh g -1 , at 20Ag -1 The lower capacity is still 185mAh g -1 ; Fig.46 This is the cycling stability diagram of the flexible battery, with a capacity retention rate of 71%; Fig.47 This is the cycle stability diagram of the flexible battery at different folding angles, and the capacity retention rate is 95%; Fig.49 Energy density and power density diagram of flexible batteries, with the highest power density reaching 227mW cm -1 The maximum energy density can reach 3.4mWh cm -1 ; Fig.52 This is the cycle stability performance diagram of the flexible battery in the air self-charging-constant current discharge mode, and the voltage can be cycled for more than 8 cycles with almost no voltage decay; Fig.53 The discharge capacity of the flexible battery under different storage time in air environment is 19 mAh g after 0.5 h of storage. -1 After 23 hours of storage, the capacity can reach 389mAh g -1 (0.5Ag -1 ); Fig.54 The capacity-voltage diagram of the flexible battery under air self-charging at different current densities. The voltage is 0.29V after 0.5h of storage and can reach 1.08V after 23h of storage. Fig.55 The discharge capacity of the flexible battery at different current densities after 23h of air self-charging. -1 The discharge capacity can reach 389mAh g -1 ,20Ag -1 The discharge capacity is still 106 mAh g -1 ; Fig.56 This is a bar chart of the discharge capacity of the flexible battery at different current densities after 23 hours of air self-charging.
Claims
1. A nitrogen-rich COF with multiple redox-active groups, characterized in that: The structural formula of the multi-oxidation-reduction active group nitrogen-rich COF is as follows: Wherein R is R1 or R2.
2. The nitrogen-rich COF with multiple redox-active groups according to claim 1, characterized in that: The multi-oxidation-reduction active group nitrogen-rich COF structural formula is:
3. A method for preparing a nitrogen-rich COF with multiple redox-active groups according to claim 1 or 2, characterized in that: The synthesis was carried out by solvothermal method using 2,6-diaminobenzo[1,2-d,4,5-d']dithiazole or 1,3,4-thiadiazole-2,5-diamine and hexaazatriphenylene hexacarboxylic acid trianhydride as raw materials in a thick-walled reaction bottle.
4. Use of the multi-oxidation-reduction active group nitrogen-rich COF according to claim 1 or 2 or the multi-oxidation-reduction active group nitrogen-rich COF prepared by the method according to claim 3 in the preparation of a positive electrode material for an aqueous zinc ion battery.
5. The use according to claim 4, characterized in that: The application of the prepared nitrogen-rich COF with multiple redox active groups in the preparation of aqueous zinc-ion batteries with air self-charging capability.
Citation Information
Patent Citations
Multi-active-site nitrogen-containing heterocyclic covalent organic framework material as well as preparation method and application thereof
CN116925355A
Polycarbonyl hexaaza-naphthalene derivative type COF material as well as preparation method and application thereof
CN114976297A
Polycarbonyl hexaazabenzophenanthrene derivative type COF for water-based zinc ion battery positive electrode material and preparation method of polycarbonyl hexaazabenzophenanthrene derivative type COF
CN116425974A